The problematic legal basis : Analysis of the Flexibility Clause as a legal basis for the proposed European Monetary Fund - Teinilä, Fanni (My University, 2019)
The European Commission proposed on late 2017 that the European Stability Mechanism would be transferred into the EU legal framework. The transfer would establish a new European agency, the European Monetary Fund (EMF). The Commission proposes that the establishment of the EMF could be based on article 352 TFEU, which is often referred to as the flexibility clause. Under article 352 TFEU the EU can take measures if they are necessary to attain one of the objectives set out in the Treaties and within the framework of the policies defined in the Treaties, even when the Treaties have not provided the necessary powers. The application of the flexibility clause would establish the EMF through secondary legislation without a Treaty amendment. However, it is not straightforward that the flexibility clause is a proper legal basis for the establishment. This thesis explores whether the EMF can be established through applying article 352 TFEU. The thesis evaluates whether the application of the flexibility clause is possible both in the EU law perspective and the Member States’ perspective. The study analyses the Commission’s proposal alongside with the different arguments favouring or opposing the application of the flexibility clause in the issue. According to the thesis, the application of the flexibility clause for the establishment of the EMF is problematic. The study finds that the principle of conferral and the limited competence in the field of economic policy may oppose the establishment of the EMF through applying the flexibility clause. As the EU can only act within the competence that the Member States have attributed to it and the competence is limited in the field of economic policy to Member States coordinating their economic policies, it is not straightforward that the EU has competence to establish EMF through applying the flexibility clause. Also, according to the thesis, the establishment of the EMF may not fulfil the conditions laid in the flexibility clause. It is required, among others, that the measure must be within the framework of the policies of the EU and the measure must be necessary to attain one of the objectives set by the Treaties. It is not straightforward that the establishment of the EMF fulfils these conditions as the status of the financial stability, which is the objective of the EMF, as EU’s objective is not evident and the framework of economic policies is limited. Also, the study claims that the establishment of the EMF through application of the flexibility clause may be in breach of the constitutional laws of Member States. According to the study, it appears that the application of the flexibility clause in the establishment of the EMF is not problem-free. At the time of writing, the legislative process remains open.
Keywords: EU constitutional law, competence, the flexibility clause, article 352 TFEU, European Monetary Fund, European Stability Mechanism